Structural anomaly of core-softened fluid confined in single walled carbon nanotube: a molecular dynamics simulation investigation. (2nd June 2016) - Pant, Shashank; Ghorai, Pradip K.
ABSTRACT: Thermodynamic and structural properties of core-softened fluid inside a (6, 6) carbon nanotube (CNT) nanopore with tunable well depth, temperature and density have been carried out by molecular dynamic simulations. Methods of analysis include the radial distribution function, translational order parameter, excess entropy and derivative of excess entropy with respect to the density. We observe strong positional ordering of core-softened fluid inside the CNT and this ordering strongly depends on temperature and density of the system. On increasing density, we observe new peaks in the positional ordering. Translational order parameter and excess entropy indicate presence of a new anomalous region. On increasing the well depth and change in slope between the attractive well and repulsive shoulder in the potential, we hardly observe any change in the anomalous regions that are drastically different from that of the bulk core-softened fluids. Abstract :